The Museological Side of the Conflict: Israeli Exhibition of Terror and the Palestinian Museum of Prisoners - Mendel, Yonatan; Steinberg, Alexa Rose (Museum and Society, 2015)
This essay deals with a section of somewhat unfamiliar terrain within the battlefield of the Israeli-Palestinian conflict: museum sites. The focus is on two museological case studies, the Palestinian Museum of Prisoners in Abu Dis and the Israeli Captured Material Display (also known as the Exhibition of Terror) in Ramat Hasharon. Through an analysis of the artistic, educational and political characteristics of both sites, one can observe the complex internal and external power relations of museums located within an ongoing conflict zone. The essay will showcase the role these institutions play in a tenacious struggle for representation amidst efforts to gain the hearts and minds of the world’s public opinion while simultaneously battling for national and communal memory. It will show that museums both serve as and perpetuate model behavior and perceptions of a political consciousness and its enemy and, in doing so, help shape political discourse. It also suggests that the study of Israeli and Palestinian museological sites can make a significant contribution to the understanding of Israeli and Palestinian collective fears, phobias, political perceptions, and desires.